A new species of Dibamus (Squamata: Dibamidae) from Pulau Simeuleu, Mentawai Archipelago, Indonesia - Das, I.; Lim, K.K.P (Zootaxa, 2009)
A new species of Dibamus from Pulau Simeuleu, off the south-west coast of Sumatra, Indonesia, is described based on material collected by Edward Jacobson and previously assigned to D. novaeguineae by de Rooij (1922). Dibamus tebal sp. nov. differs from all congeners in showing the following combination of characters: SVL 133.5 mm, body relatively robust, body width 4.9% SVL, postoculars two, midbody scale rows 24, scales around neck 24, scales around vent 15, ventrals 186, subcaudals 42, frontonasal entire, rostral suture incomplete, labial and nasal sutures complete, two pairs of preanal pores, nuchal collar or body band absent, presacral vertebrae 119, postsacral vertebrae 26, and a relatively longtail (18.6% SVL).